Neural network and PSO-based structural approximation analysis for blade of wind turbine. (1st January 2013) - Wang, Lei; Hu, Pin; Lu, Jingui; Chen, Fengxin; Hua, Qi
Structural approximation analysis is important for optimisation design of blade of wind turbine. The neural network is applied to construct the model of structural approximation analysis for blade of wind turbine in this paper. The approximation analysis on the blade of wind turbine can be performed based on the model of neural network. The back-propagation algorithm and particle swarm optimisation algorithm are applied to train the patterns of approximation analysis for blade of wind turbine, and the neural network-based model can be obtained in this paper. The training procedure of constructing the model of neural network via back-propagation algorithm and particle swarm optimisation algorithm will be discussed in this paper. The numerical example will be given finally in this paper.